2005
DOI: 10.1038/ng1540
|View full text |Cite|
|
Sign up to set email alerts
|

A functional variant in FCRL3, encoding Fc receptor-like 3, is associated with rheumatoid arthritis and several autoimmunities

Abstract: Rheumatoid arthritis (RA) is a common autoimmune disease with a complex genetic etiology. Herein we identify a single-nucleotide polymorphism (SNP) in the promoter region of FcRH3, a member of the Fc receptor homolog family, that is associated with RA susceptibility (OR=2. 15, P=0.00000085). This polymorphism alters the binding affinity of nuclear factor-κB and regulates NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Author ManuscriptFcRH3 expression. High FcRH3 expression on B-cells and augmented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
330
11
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(359 citation statements)
references
References 49 publications
17
330
11
1
Order By: Relevance
“…18,19 Interestingly, FCRL3, a member of this family in humans, is associated with RA and other autoimmune conditions, including lupus. 20 We are currently investigating whether one or both of these genes present allelic differences between NZW and B6. If it were the case, it would be possible that these genes could indirectly regulate Fcrg2b on GC B cells.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Interestingly, FCRL3, a member of this family in humans, is associated with RA and other autoimmune conditions, including lupus. 20 We are currently investigating whether one or both of these genes present allelic differences between NZW and B6. If it were the case, it would be possible that these genes could indirectly regulate Fcrg2b on GC B cells.…”
Section: Resultsmentioning
confidence: 99%
“…19 Interestingly, FCRL3 has been recently associated with susceptibility to GD. 9,20 A different (CA) repeat polymorphism located in the 3 0 region of NFKB1 has been reported to be associated with T1D but subsequent studies were unable to confirm this finding. [21][22][23] In this study, the frequency of the D allele in control populations were similar to those observed in other Caucasian populations, as reported by Karban (39%).…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowiczmentioning
confidence: 99%
“…In that study, an SNP (runx1) of RUNX1 on 21q22.3 was also associated with RA. Kochi et al 12 showed an association of a functional SNP at position À169 (fcrh3_3) in the promoter region of Fc receptor-like 3 (FCRL3) on 1q21-23 with RA. This SNP altered the binding affinity for nuclear factor-kB and regulated the expression of FCRL3 mRNA.…”
Section: Introductionmentioning
confidence: 99%